Appropriateness of Algerian Higher Education Quality Assurance System to Educational Institutions: A Teaching staff's Perspective - Abdelkader Benaissa Cherif (University of Science and Technology, Yemen, 2017)
The aim of this study was to investigate the procedures taken by the Algerian authorities for establishing a quality assurance system in higher education, officially declared in June 2008, and to examine the relevance of such procedures to the higher education system in the country. To achieve this objective, a questionnaire was designed and distributed to a sample of 100 professors from the disciplines of economics, business studies and management sciences, during the period from 04 November to 17 December 2015. The study results revealed that the professors agreed that all the objectives, procedures, and scope of the quality assurance system were in line with the suggestions and recommendations of local and international expert committees.  However, mechanisms of implementing quality assurance system have excluded  certain important effective mechanisms temporality because they would have negative consequences on higher education in the current situation.    Keywords: Accreditation, Evaluation, Higher education in Algeria, Quality, Quality assurance,  Quality assurance mechanisms